HateSpeak in contemporary Arabic discourse - Mazīd, Bahāʼ al-Dīn Muḥammad (Cambridge Scholars, 2012)
"HateSpeak in Contemporary Arabic Discourse fills in an obvious gap in discourse studies on Arabic. After a detailed semantic and metaphorical account of hate in English and its equivalents in Arabic and an exploration of the causes of hate, the book illustrates major cases of hate and HateSpeak in contemporary Arabic discourse - Arabs vs. Israel, Sunni vs. Shi'ites, Ahly vs. Zamalek, Egypt vs. Algeria, Men vs. Women, Rebel vs. Mainstream, and Sa'idi vs. Cairene, There is a separate section on HateSpeak in Arabic in the context of the revolutions in many Arab countries--"the Arab Spring"--With a focus on Egypt. The book contains a number of apt and interesting digressions on hate in general and hate in Arabic in particular and a discussion of the issues involved in translating HateSpeak in Arabic. The ultimate goal is not to celebrate hate and HateSpeak, not to side with any party at the expense of another, but to provide a diagnosis followed by a number of remedies that may help convert HateSpeak into HeartSpeak"--Provided by publisher.